The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.ijscr.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment for adult inguinal hernia with cryptorchidism: A case report

Abstract: Highlights Cryptorchidism is the most common disorder of male children, which is often diagnosed and treated during childhood. A case of adult inguinal hernia with cryptorchidism is rare condition. TAPP and simultaneous laparoscopic orchiectomy for inguinal hernia with cryptorchidism were safe and feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The inclusion criteria for this study were as follows: [ 1 ] adult males, [ 2 ] patients with unilateral/bilateral cryptorchidism, and [ 3 ] patients with a strong desire to procreate or a strong desire for testicular preservation. The exclusion criteria in this study were as follows: [ 1 ] significant testicular atrophy revealed through laparoscopic exploration; [ 2 ] undescended testes with evidence of deterioration; [ 3 ] comorbid severe cardiovascular disease, diabetes mellitus, liver dysfunction, renal disease, and severe hematological disorders; and [ 4 ] contraindications to general anesthesia. We identified 37 adult cryptorchidism patients aged 30.92 ± 9.1 years between November 2017 and February 2022 (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria for this study were as follows: [ 1 ] adult males, [ 2 ] patients with unilateral/bilateral cryptorchidism, and [ 3 ] patients with a strong desire to procreate or a strong desire for testicular preservation. The exclusion criteria in this study were as follows: [ 1 ] significant testicular atrophy revealed through laparoscopic exploration; [ 2 ] undescended testes with evidence of deterioration; [ 3 ] comorbid severe cardiovascular disease, diabetes mellitus, liver dysfunction, renal disease, and severe hematological disorders; and [ 4 ] contraindications to general anesthesia. We identified 37 adult cryptorchidism patients aged 30.92 ± 9.1 years between November 2017 and February 2022 (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cryptorchidism is usually diagnosed and treated in childhood, and adult patients with cryptorchidism are relatively rare. Current literature reports on treating cryptorchidism in adults are scarce, and most are case reports [ 3 – 6 ]. In this study, we investigated the safety and efficacy of laparoscopic orchidopexy for the treatment of cryptorchidism in adults to highlight the technique and outcomes.…”
Section: Introductionmentioning
confidence: 99%